Pengembangan Bahan Ajar Untuk Meningkatkan Pemahaman Materi Mata Kuliah Demografi Teknik - - Trisnawati (Jurnal Ekonomi dan Pendidikan, 2007)
Problems of this research are the difficulty of collage students to understand technique demography study material and the unavailability of appropriate teaching material. This research is aimed to increase college student understanding toward technique demography study material and study achievement. Developing material of teaching was done by: (1) Product analyzed by reducing and increasing study material; (2) Wrote material of teaching; (3) Expert validation and revised, by material of teaching expert, instructional developing, study evaluation, demography and environmental expert; (4) Small group test and revised, toward 10 collage student of geography field study; and (5) Large scale of field survey test and final product, on odd semester 2006/2007, toward 30 collage student of geography field study, FKIP, Lampung University.Pre test and post test was done in every study. The using of teaching study and doing exercise question or task in the last meeting are used in this research. The result are: (1) The increasing of college student understanding toward technique demography study material, average score in post test higher (57,76) than average score in pre test (30,42); (2) There is a significant relationship between understanding level with collage student study achievement, r-count (0,396) higher than r-table (0,361) in significant level 5% and N = 30.